Pandemic Effects on 21st-Century Skills Utilization Among Business and Management Students: Basis for Skills Enhancement - Tandoc, Melba (JPAIR Institutional Research, 2026)
The outbreak of COVID-19 pandemic severely affected international education systems, with advocated for 21st-century skills among tertiary students remaining principles at risk. One of the research objectives was to explore how the outbreak (of pandemic) influenced Business and Management students - from Palawan State University-Palawan College of Arts and Trades (PSU-PCAT) - in using 21st-century skills of learning, earning basis for their improvement. A descriptive-quantitative research design was used, using a validated researcher-made questionnaire based on the 21st-century skills framework (Learning, Literacy and Life Skills). Respondents were chosen through proportional stratified random sampling and totaled 310 students (50% from each program) during the First Semester of Academic Year 2023-2024. Frequency, percentage, and weighted mean were used to analyze data. The results showed that an overall mean of students agreed regarding a positive use of 21st-century skills across all subdomains: a mean score of 2.78 in Learning Skills, 2.73 in Literacy Skills and 2.78 in Life Skills was found. Learning and Life Skills domain received the highest mean scores among the three categories, indicating that students perceived stronger growth in their critical thinking, adaptability, leadership abilities, and problem solving. These results suggest that, despite the challenges of emergency remote learning, students perceived important 21st-century skills were maintained over the pandemic period. The findings highlight the importance of focused skills development initiatives that can enhance students' skillsets from moderate agreement with abilities to mastery in practical digital literacy and applied critical inquiry.
Keywords: Education; K to 12; Life skills; literacy skills; learning skills and perceptions